Talking to Foreign Fighters: Insights into the Motivations for Hijrah to Syria and Iraq. (4th March 2017) - Dawson, Lorne L.; Amarasingam, Amarnath
ABSTRACT: Little of the discussion of foreign fighters in Syria and Iraq is informed by primary data derived from talking with the foreign fighters. This article reports some initial findings from interviews with twenty foreign fighters in Syria. The findings are compared with three other recent studies of European foreign fighters, and aspiring fighters, based on some primary data. While those studies emphasize the role of low social and economic prospects in motivating the choice to go, this study found little evidence of such factors, and alternatively argues more attention should be given to existential concerns and the role of religiosity. Consideration is also given to the methodological challenges posed by using of terrorists' accounts of their motivations.